2014
DOI: 10.1002/dc.23100
|View full text |Cite
|
Sign up to set email alerts
|

Utility of brachyury in distinction of chordoma from cytomorphologic mimics in fine‐needle aspiration and core needle biopsy

Abstract: Chordoma is a neoplasm of notochordal differentiation that typically occurs in the axial skeleton. Accurate diagnosis is therapeutically important but can be challenging, especially in fine-needle aspiration (FNA) and core needle biopsy (CNB). Immunohistochemistry for the transcription factor brachyury (T) has recently proven diagnostically useful in whole-tissue sections. Our aim was to compare brachyury performance with conventional markers (S-100, EMA, keratin) and to evaluate its utility in distinguishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Recent research, however, has shown the transcription factor brachyury to be a highly specific and reliably sensitive marker for identification of chordoma in humans, particularly when used in conjunction with cytokeratin. 19,20,38 In the current study, the neoplasms in PKB mice and the positive-control ferret chordoma exhibited strong nuclear immunoreactivity for brachyury and cytoplasmic immunoreactivity for cytokeratin, supporting the diagnosis of chordoma and suggesting that brachyury is a viable marker for chordomas in PKB mice. It was not clear why decalcified primary masses exhibited cytoplasmic immunoreactivity to brachyury.…”
Section: Discussionsupporting
confidence: 71%
“…Recent research, however, has shown the transcription factor brachyury to be a highly specific and reliably sensitive marker for identification of chordoma in humans, particularly when used in conjunction with cytokeratin. 19,20,38 In the current study, the neoplasms in PKB mice and the positive-control ferret chordoma exhibited strong nuclear immunoreactivity for brachyury and cytoplasmic immunoreactivity for cytokeratin, supporting the diagnosis of chordoma and suggesting that brachyury is a viable marker for chordomas in PKB mice. It was not clear why decalcified primary masses exhibited cytoplasmic immunoreactivity to brachyury.…”
Section: Discussionsupporting
confidence: 71%
“…Our case of secondary chordoma demonstrated epithelioid cells with vacuolated cytoplasm and round nuclei with small nucleoli amid a background of chondromyxoid extracellular matrix. Our diagnosis of this secondary chordoma is based on the patient's known history of a clival chordomas, 3.5 years before salivary gland involvement, and positive immunohistochemical staining for brachyury and SOX9 of the tumor cells …”
Section: Discussionmentioning
confidence: 99%
“…Our diagnosis of this secondary chordoma is based on the patient's known history of a clival chordomas, 3.5 years before salivary gland involvement, and positive immunohistochemical staining for brachyury and SOX9 of the tumor cells. 45,46…”
Section: Smsgs With Diagnostic Difficulties and Rare Smsgsmentioning
confidence: 99%
“…The Brachyury gene is also implicated in various human carcinomas and could be responsible for the epithelial-mesenchymal transition allowing tumors to metastasize 2225 . In addition, the uniquely high levels of expression of the Brachyury protein in chordomas have allowed scientists and labs to differentiate them from other tumors of the neuroaxis, such as chondrosarcomas, with relatively high sensitivity and specificity 2631 . The degree of Brachyury expression, however, has not shown a prognostic indication in chordomas 32 .…”
Section: Pathogenesis and Geneticsmentioning
confidence: 99%